AB0098 Peroxisome proliferator-activated receptor-gamma coactivator-1Β facilitates migration and invasion of fibroblast-like synoviocytes in rheumatoid arthritis via activation of canonical and non-canonical nf-Κb signalling pathway. (12th June 2018) - Ma, J.-D.; Yan, T.; Mou, Y.-S.; Jing, J.; Mo, Y.-Q.; Dai, L.
Abstract : Background: Fibroblast-like synoviocytes (FLS) in rheumatoid arthritis (RA) manifest tumor-like properties including increased proliferation, prolonged survival, apoptosis resistance, adherence and invasiveness of adjacent tissues. Peroxisome proliferator-activated receptor-gamma coactivator-1 (PGC-1) β is a transcriptional coactivator which plays important roles in regulating energy metabolism and cytokine signalling pathways. Our previous study showed that elevated PGC-1β expressed in RA-FLS promoted their pro-inflammatory effect. However, the roles of PGC-1β on regulating migration and invasion of RA-FLS remains to be identified. Objectives: To investigate the role of PGC-1β on regulating migration and invasion of RA-FLS and underlying mechanism. Methods: Synovial tissues were obtained by closed needle biopsy from six patients with active RA and FLS were isolated and cultured. PGC-1β in RA-FLS was down-regulated or over-expressed by lentivirus with same vectors marked Lv-sh-GFP or Lv-GFP as negative controls. Effects of PGC-1β on migration and invasion capacity were detected by wound healing assays and transwell migration and invasion assays. The change of proteases in culture supernatants were detected by Proteome Profiler human protease array kit (R and D Systems, USA) and verified by qRT-PCR and western blot. The expression of key signalling molecules in canonical and non-canonical NF-κB signalling pathway was detected by western blot. Results: Down-regulation of PGC-1β by Lv-sh-PGC-1β transfection inhibited migration and invasion of RA-FLS compared with Lv-sh-GFP transfection group (wound healing: 1252±214 vs. 764±184 µm, p<0.001; migration: 184±74 vs. 642±32 cells/field, p<0.001; invasion: 124±47 vs. 445±67 cells/field, p<0.001), while over-expression of PGC-1β promoted migration and invasion of RA-FLS (all p<0.05, figure 1A C). Down-regulation of PGC-1β in RA-FLS significantly decreased the expression of MMP-3 and MMP-9 in the culture supernatant which was measured by Proteome Profiler human protease array (MMP-3: p=0.032, MMP-9: p=0.037). Further qRT-PCR and western blot analysis verified that both mRNA and protein expression of MMP-3 and MMP-9 in RA-FLS were significantly decreased compared with Lv-sh-GFP transfection group (all p<0.05, figure 1D). Down-regulated PGC-1β in RA-FLS significantly suppressed the expression of NF-κB p65, NF-κB p-p65, RelB and NIK in protein level, while over-expression of PGC-1β promoted the expression of NF-κB p65, NF-κB p-p65, RelB and NIK (all p<0.05, figure 1E). Conclusions: Our findings suggested that PGC-1β facilitates the migration and invasion capacity and MMP-3/9 expression in RA-FLS through activation canonical and non-canonical NF-κB signalling pathway. Acknowledgements: This work was supported by National Natural Science Foundation of China (no. 81471597 and 81671612), Guangdong Natural Science Foundation (no. 2016A030313307, 2017A030313576 and 2017A030310236) and Guangdong Medical Scientific Research Foundation (no. A2017109). Disclosure of Interest: None declared